Grameen Bank and its Sister Organizations-Grameen Chek and Grameen Krishi (Agricultural) Foundation Not Only Providing Credit: They Guide the Landless Families in Bangladesh for their Development (Global Journal of Management and Business Research, 2014)
This paper talks about Grameen Bank (GB) micro financing program features, strategies, policies and its two other sister organizations Grameen Chek (GC), involves in manufacturing handloom garments and Grameen Krishi (Agricultural) Foundation (GKF), engages in agricultural activities and irrigation management in Bangladesh. All are social business organizations in Bangladesh. GKF runs its farms 'no loss basis'. Grameen Bank and Grameen Chek run their programs without receiving external funding; rather these two organizations have operated their programs from their own generated funds. Moreover, Grammen Bank and Grameen Chek are free from external consultants` pressure rather they are developing their programs, policies and implementation strategies by using their in-house staff skills and experience.
Keywords: external consultants; external funding; grameen bank; grameen chek; grameeen krishi foundation; internal funding; empowerment; implementation strategi